Selfassessment of finalyear undergraduate physiotherapy studentsâ€™ literaturesearching behaviour selfperceived knowledge of their own critical appraisal skills and evidencebased practice beliefs - D Hess; J Frantz (South African Medical Association, 2016)
Background. Health professionals and new graduates alike are expected to be efficient in applying evidence-based practice. Research and evidencebasedpractice skills are taught in the research modules at university, but it is not clear whether students translate those skills into clinical practice.Objective. To determine the self-assessment literature-searching behaviour, self-perceived knowledge of critical appraisal skills and evidence-basedpractice beliefs of final-year undergraduate physiotherapy students at a university in South Africa.Methods. This study used a quantitative approach, with a small qualitative component. A convenience sample of the final-year undergraduate physiotherapyÂ students (N=36) registered for the 2012 academic year was approached to participate in the study. Data were collected using an existing questionnaire.Results. The study yielded a 75% response rate. With regard to literature-searching skills, 30% searched for literature more than once a week, 52%searched only for specific information and most had access to literature. Students received their information from journal articles (85%), the internetand databases. They were slightly confident when it came to literature appraisal and believed that evidence-based practice was essential to their practice(96%), but expressed a need for more training (59%). Their understanding of the evidence-based practice concept was limited because they based theirtreatment choices on content and other role-models, and related their choices to their previous patient experiences.Conclusion. Students believed that evidence-based practice was vital, yet their understanding of the concept was restricted when compared with theliterature and they expressed a need for further training.